Structure of photoluminescence DL-spectra and phase transformation in lightly doped SiC crystals and films - Vlaskina, S.I.; Mishinova, G.N.; Vlaskin, V.I.; Rodionov, V.E.; Svechnikov, G.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
In this work, the results of investigations of DLi spectra in α-SiC crystals and films with a low impurity concentration have been presented. Photoluminescence spectra of lightly doped SiC single crystals and films with the impurity concentration of ND–NA ~ (2…8)∙10¹⁶ cm⁻³, ND ~ (5…8)∙10¹⁷ cm⁻³, and ND–NA >3∙10¹⁷ cm⁻³, ND ≥ 1∙10¹⁸ cm⁻³ (NDLsamples) were investigated within the temperature range 4.2…77 K. Complex spectroscopic study of one-dimensional disordered structures caused by solid phase transformations in SiC crystals was presented. Disordered growth D-layers in lightly doped crystals and α-SiC films were investigated using low temperature photoluminescence. The analysis testifies that DL and SF spectra hand-in-hand follow the structure transformations. It has been shown that the DL and SF spectra of luminescence reflect the fundamental logic of SiC polytypes structure. This allows to observe the structure changes at the phase transformations, the growth of SiC polytypes and to control their aggregates.